SEGMENTASI METERAN LISTRIK MENGGUNAKAN METODE ADAPTIF (Information Technology and Telematics, 2013)
Electricity is become more and more important lately. Most of human daily tools are moved by it. So there's must be someone or in this case some company that taking full reponsibility and control of it. It is PLN, a goverment company that has the authority to handle all of it, from installment to monthly payment and etc. Each month, this company delegate their officcer to visiting each house or building that using its service. The officcer will write down the numbers based from the electricity meters. The amount of payment is depend on the number itself.There are better ways to colecting the data instead of this one. Instead of writting down the data, how about capturing the image of electricity meters and then let the application do the furthe analysis. In this case, the application will do some segmentation with the image and as a result, the final image only show the numbers and black out the onther part of the image.keywords : Electricity, Electricity meters, data, image, Segmentation